2000
DOI: 10.1046/j.1365-2524.2000.00249.x
|View full text |Cite
|
Sign up to set email alerts
|

Citizens Advice Bureaux in general practice: an illuminative evaluation

Abstract: A number of Citizens Advice Bureaux (CAB) have entered into partnerships with Health Authorities in order to provide advice in general practice surgeries as part of the health care services offered by the primary health care team. This illuminative evaluation has involved an exploration of the impacts of the service from the perspective of its users, the CAB advisers and the referral agents. Data was collected from questionnaires, individual interviews and focus group interviews from participants in both a rur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 6 publications
(6 reference statements)
0
33
0
Order By: Relevance
“…We propose the following two strategies to improve caregivers’ access to financial and other support; to increase an awareness of the existing resources, but also to tackle gender discrimination. One strategy in improving immigrant caregivers’ access to welfare support is to increase the awareness of general practitioners and other health practitioners about caregivers’ gender‐determined barriers in accessing support (Galvin et al. 2000, Nankervis et al.…”
Section: Resultsmentioning
confidence: 99%
“…We propose the following two strategies to improve caregivers’ access to financial and other support; to increase an awareness of the existing resources, but also to tackle gender discrimination. One strategy in improving immigrant caregivers’ access to welfare support is to increase the awareness of general practitioners and other health practitioners about caregivers’ gender‐determined barriers in accessing support (Galvin et al. 2000, Nankervis et al.…”
Section: Resultsmentioning
confidence: 99%
“…2002). Evaluations suggest that the schemes complement the work of the primary healthcare team, allow easier access to services, and are particularly beneficial for older people who are reluctant to use community advice centres (Galvin et al . 2000, Sherratt et al .…”
Section: The Consolidated Prevention Practice Proposalsmentioning
confidence: 99%
“…1999, Emanuel & Begum 2000). Service users have reported various barriers to using high street services: geographical distance, especially in rural areas, lack of clarity about how to access the service, long waiting times, and lack of continuity in advisers (Galvin et al . 2000).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that the service reaches people with particular needs; for example, older people (Abbott & Hobby 1999, Moffat et al . 1999), people with depression (Galvin et al . 2000) or those with complex problems (Middleton et al .…”
Section: Introductionmentioning
confidence: 99%